Perancangan Dan Aplikasi Pembangkit Plasma Tegangan Tinggi AC Menggunakan Dual Flyback Transformer Topologi Inverter Push-Pull - Faisal Setiawan; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In this study, a laboratory-scale prototype of high-voltage plasma generator has been realized. This generator intends to have the capability to employ corona plasma which is used as an application medium for the decomposition of coconut shell waste carbon material into graphene. The design of the high voltage generator prototype is divided into three main parts, the first isa full wave rectifier with a 12 volt CT used as a unidirectional power supply in the inverter driver control circuit, and the design of a switch module power supply (SMPS) prototype with adjustable voltage 0-50 volts are used as the unidirectional input voltage in the push-pull inverter power circuit. Furthermore, the second is the inverter control circuit using the TL494IC as a MOSFET triggering frequency oscillator driver, and using a pulse transformer isolator as an electrical isolator as asafety between the control circuit and the power circuit in the push-pull inverter, and the third is the inverter power circuit design on the This research is designed with a push-pull inverter topology using a MOSFET as an alternating current switching electronic switch. This device operates when connected to a ferrite core TV Flyback Transformer which is able to work at high frequencies with a winding ratio 1 : 75 as a fast transformer to raise it to a high voltage with a plate-rod electrode configuration. The success of the corona plasma appearance depends on the voltage and electric currents, as wellas the distance between the electrodes. Meanwhile, the amount of plasma discharge stress on the carbon material is directlyproportional to the success of producing graphene. The higher the exposure of the plasma discharge stress to the carbon material, the greater the success of producing graphene. Tests carried out by varying the input voltage of the inverter from 9,0 volt, 13,9 volt and 19,5 Volts AC. Based on the results of the Transmission Electron Microscope (TEM) test, the best resultsfor the formation of graphene structures are the inverter voltage variation of 19,5 volts AC for 5 minutes and the electrodedistance of 10mm with the highest voltage of 2,77 kV at 54,82 kHz.Keyword : Push-Pull, Flyback TV Transformer, graphene